Short- and long term follow-up of 150 sports horses diagnosed with tendinopathy or desmopathy by ultrasonographic examination and treated with high-power laser therapy. (August 2018) - Pluim, M.; Martens, A.; Vanderperren, K.; Sarrazin, S.; Koene, M.; Luciani, A.; van Weeren, P.R.; Delesalle, C.
Highlights: High-power laser therapy can be safely used in horses. A significant amelioration of lameness and ultrasound scores after high-level laser therapy. Re -injury rate within the lower ranges of previously published studies on several other treatment modalities. A rapid build-up of the rehabilitation program in high-power laser treated horses.